2011
DOI: 10.1017/s1368980011002163
|View full text |Cite
|
Sign up to set email alerts
|

Tailored nutrition education: is it really effective?

Abstract: Objective: There has been a growing interest in tailored nutrition education over the previous decade, with a number of literature reviews suggesting this intervention strategy holds considerable potential. Nevertheless, the majority of intervention trials undertaken to date have employed subjective self-report outcome measures (such as dietary recalls). The aim of the present review is to further consider the likely true effect of tailored nutrition education by assessing the findings of tailored nutrition ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This is evidenced by the fact that up to 63% of the households never attended any nutrition education while only 24 and 14% received nutrition education once and twice, respectively. Multiple attendance of nutrition education has been shown to improve nutrition knowledge (Eyles & Mhurchu, 2011; Pomerleau, Lock, Knai, & McKee, 2005). Lack of correlation between nutritional knowledge and attitude revealed by the current study deviates from the findings of other nutrition‐related studies conducted before.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the fact that up to 63% of the households never attended any nutrition education while only 24 and 14% received nutrition education once and twice, respectively. Multiple attendance of nutrition education has been shown to improve nutrition knowledge (Eyles & Mhurchu, 2011; Pomerleau, Lock, Knai, & McKee, 2005). Lack of correlation between nutritional knowledge and attitude revealed by the current study deviates from the findings of other nutrition‐related studies conducted before.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the limited number of studies and study variability no conclusive findings could be drawn. A second review examined the effectiveness of tailored nutrition education on objective outcome measures only [6]. There were substantial differences in the theoretical underpinnings of the interventions applied in the four included studies.…”
Section: Introductionmentioning
confidence: 99%
“…Even with very hands-off POP interventions, such as in-store marketing or menu labelling, some studies have observed an impact on consumer behaviour 17 , 26 . On balance, however, much more research is needed on the most effective methods of changing food-purchasing behaviour, including further evaluation of more tailored approaches such as this one 19 , 20 , 26 . Compared with an ecological approach, our tailored approach of multiple sessions with a dietician requires more time commitment from the dietician and patient.…”
Section: Discussionmentioning
confidence: 99%
“…taxation, altered signage, healthier check-out aisles) are not easily tailored to individual health needs. There is considerably less evidence available on interventions where registered dieticians or health educators conduct sessions with individual consumers in the grocery store or supermarket 20 . In part, this could be due to the perceived resource-intensity of such programmes.…”
Section: Introductionmentioning
confidence: 99%